Development of the Electronic Service Implementation Plan (ESIP-ERPL) counseling management system for guidance and counseling program implementation plans in schools - Guspriadi, Yan; Ardi, Zadrian (Universitas Negeri Padang, 2023)
Indonesia is the 4th the most populous country in the world after China, India and the United States. So that the State of Indonesia is included in one of the developing countries in the world. However, in scientific publications, Indonesia ranks 48th in the world. This encourages researchers' interest in assessing the psychological condition of Indonesian students in writing, because writing skills is not only cognitive but also emotional activities. The purpose of this study was to describe the anxiety conditions of Indonesian students in writing based on gender, ethnicity, province, department, university, and writing experience. This type of research is descriptive. The research sample is 1002 respondents consisting of eight ethnic groups in Indonesia. The data in this study are 5-point Likert scale politomy data collected using the writing apprehension scale. The instrument consisted of 26 statements of general anxiety about writing, teacher writing evaluations, peer writing evaluations, and professional evaluations (e.g., publishers and magazine editors) administered online. The research data were analyzed using the Rasch model using variable maps, and subtotal specifications. The findings show that there is no difference in anxiety of male and female students in writing, students who have never written will experience more writing anxiety than students who have written. Thus, students who have written but have not finished writing a paper will also experience writing anxiety.